Effect Of The Quality Of Mulberry Leaves Morus alba Against The Silkworm Nutrition Index Bombyx mori L. (Lepidoptera:Bombicidae) - Masitta Tanjung (International Journal of Ecophysiology, 2021)
Th leaf quality effect of mulberry (Morus alba) on nutrition index of silkworm (Bombyx mori L.) has been studied. This research was design according to Completely Randomized Design (CRD) with 2 treatments which are an unfertilized mulberry plant, and the fertilized mulberry plants with urea, triple super phosphate (TSP), nitrogen, phosphor, and potassium (NPP). Twenty times replications was applied for each treatment. The results showed that the leaf of fertilized mulberry plant is evidently increased the growth and the consumption rate on the conversion efficiency of instar III, the feed digestion of instar V, the efficiency of food conversion of instar IV and V, and the estimate of feed digested of instar IV with the number for each was 36% and 26%, 30%, 34% and 67%, 24%, respectively.Bombyx mori L.